Pricing of Risk, Various Volatility Dynamics and Macroeconomic Exposure of Firm Returns: New Evidence on Age Effect - Khan, Faisal; Rehman Khan, Saif Ur; Khan, Hashim (International Journal of Economics and Financial Issues, 2016)
While investigating the role of age effect in detecting the risks-return tradeoff, various volatility dynamics and macroeconomic exposure of firm returns, this research study employs monthly data from Pakistani stock market for the period from 1998 to 2012. For this purpose, three generalized autoregressive conditional heteroskedasticity models were functioned: GARCH-M for risks-return tradeoff, GARCH (1, 1) for capturing different volatility dynamics and EGARCH for asymmetric and leverage effect. This study rests on the following outcomes. Firstly, we unravel that age effect is flag rising in the debate of risks-return tradeoff. Secondly, in the course of exploring whether the firm age matters from the context of asymmetry and leverage effect, we find that it is certainly the case. Thirdly, age effect holds considerable role in determining various volatility dynamics. Finally, we expose that macroeconomic variables affect stock returns differently depending upon firm age, signifying the role of age effect. Keywords: firm age, risks-return trade-off, volatility dynamic and macroeconomic exposure. JEL Classifications: G10, G11, G12